Pelaksanaan Literasi Kewarganegaraan Siswa Di SMA Kabupaten Simeulue Dalam Era Globalisasi - Hidayat, Roni (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
This study examined the implementation of civic literacy at Simeulue High School. It used qualitative research methods to analyze social symptoms and behaviors in order to understand and improve student civic literacy. The study focused on 5 civic education teachers as informants. Data were collected through observation, interviews, and documentation. The results suggested that student civic literacy could be improved through the implementation of curriculum, including lesson plan design and the use of elaborative learning models. The professionalism of teachers also played a vital role in enhancing civic literacy. Additionally, the study suggested that literacy corner activities at school can further enhance civic literacy. However, there were some challenges related to the implementation of student civic literacy at Simeulue High School.